If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 5x + -5 Reorder the terms: 7 + -3x = -5 + 5x Solving 7 + -3x = -5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + -3x + -5x = -5 + 5x + -5x Combine like terms: -3x + -5x = -8x 7 + -8x = -5 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + -8x = -5 + 0 7 + -8x = -5 Add '-7' to each side of the equation. 7 + -7 + -8x = -5 + -7 Combine like terms: 7 + -7 = 0 0 + -8x = -5 + -7 -8x = -5 + -7 Combine like terms: -5 + -7 = -12 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| 4(3s+9)=168 | | 6(2k+1)-6k-2=14.016 | | 180-8x+2= | | 0=3/4x+3 | | -3n-6=15 | | 16x^2-2=79 | | 4(2l+1)=84 | | (6-2i)+(11+6i)=0 | | 20x-80y=0forY | | 70+60(8x+2)= | | 3(a-6)=42 | | y/2.5=5 | | xsquared+3x-8=0 | | -8(2t+1)=-24 | | (4-6i)(6-8i)=0 | | m/5-2=-12 | | -3(3x-5)=-14 | | 3(f-9)=-18 | | 3t+8=52 | | 3=-2+25 | | x*x-1x-12=0 | | x^3-bx^2-c=0 | | x/3+1=x/2-3 | | 5.9a+10=80.8 | | x+19=2x+19 | | K^2-4k-32=0 | | 14-5x=8-2x | | -9(-x-4)=-45 | | ax^3-bx^2-c=0 | | 48=5f+23 | | -20x-33=-7 | | 5m+3=23 |